Old State, New Governance: The Transformation of Prokopim in Yogyakarta City Government - Dimas Bangun Setyawan; Supardal Supardal (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2025)
This research aims to determine the Governance of the Leadership Protocol and Communication Section in Supporting Good Governance in the Yogyakarta City Government and the Challenges of the Leadership Protocol and Communication Section in Arranging Official Events for the Yogyakarta City Government by applying resource-based view and excellence and public theory. relations (two way asymmetrical). This type of research is qualitative descriptive research which aims to examine the governance and challenges of arranging events in the Protocol and Communication section of Yogyakarta City Leadership. Research data was collected through observation, interviews and government activities related to direct service to the leadership as well as being a communication medium between the government and the community. This study also highlights the importance of human resources and communication which highlights the need for effective communication and public relations to encourage good governance in the government sphere and since the beginning Prokopim has implemented a Resource strategy (Resource-based view) and Excellence and Public Relations Theory (two way Asymmetrical) to increase work efficiency and improve services to leaders and the community. These two things aim to ensure that the Prokopim department's services to regional leaders run well and ensure that the Prokopim remains responsive to community aspirations in order to realize good governance in the Yogyakarta City government. In this way, the application of resource theory and excellence and public relations theory can be considered capable of realizing the desired good governance.